An adaptable Health Impact Assessment (HIA) framework for assessing health within Environmental Assessment (EA): Canadian context, international application. Issue 1 (2nd January 2018) - McCallum, Lindsay C.; Ollson, Christopher A.; Stefanovic, Ingrid Leman
Abstract: One of the most widely used approaches for assessing environmental effects of large-scale projects is Environmental Assessment (EA). Recently, there has been a focus on including broader health impacts as part of the EA process. One of the tools available to achieve this is Health Impact Assessment (HIA). In order to address the issue of developing a consistent and transparent method for HIA, an assessment framework was developed with the intention of: (1) ensuring that the framework can be used as a stand-alone process and when integrated with EA; (2) applying language to closely align with EA processes; and, (3) devising a system for evaluating overall impact when a multitude of determinants are considered. The Assessment Framework is presented along with a decision matrix to help to determine potential significance of health outcomes. It also provides a process for characterization of effects and identifies whether outcomes are significant. By using an HIA Framework, a well-known yet underutilized tool can effectively address health issues within the EA process, both in a Canadian context and internationally.